Women's Political Representation and Intimate Partner Violence - S Anukriti; Bilge Erten; Priya Mukherjee (Institute of Labor Economics (IZA), 2022)
We estimate the impact of female leaders on intimate partner violence experienced by women in districts from which they are elected. Exposure to female leaders in state legislatures in India increases the likelihood that female constituents in rural areas report experiencing physical violence from their husbands. This effect can be explained by an increase in women's modern contraceptive use—resulting from improvements in public provision of health services in exposed districts—which leads to marital conflict, especially when the husband has a stronger preference for sons relative to the wife.
Keywords: D72; J16; J13; 330; intimate partner violence; female leaders; elections; India; contraception; representation